2012
DOI: 10.1155/2012/403908
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress and the Cutaneous Immune Response: Roles of the HPA Axis and the Sympathetic Nervous System in Atopic Dermatitis and Psoriasis

Abstract: Psychological stress, an evolutionary adaptation to the fight-or-flight response, triggers a number of physiological responses that can be deleterious under some circumstances. Stress signals activate the hypothalamus-pituitary-adrenal (HPA) axis and the sympathetic nervous system. Elements derived from those systems (e.g., cortisol, catecholamines and neuropeptides) can impact the immune system and possible disease states. Skin provides a first line of defense against many environmental insults. A number of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 108 publications
(118 reference statements)
3
115
0
7
Order By: Relevance
“…However, the mechanisms underlying the triggering or aggravation of acne by stress remain unclear, although possible mechanisms have been proposed. For instance, stress induces secretion of different neurotransmitters, cytokines, and hormones-CRH, cortisol, glucocorticoids-which have skin receptors and can aggravate several skin diseases [34,37,51,55,66] including acne [77,78]. Interesting, a recent study showed that skin diseases influence emotional status, through chemical mediators released by epidermal keratinocytes [22].…”
Section: Stress and Skin: A Specific Mechanismmentioning
confidence: 99%
“…However, the mechanisms underlying the triggering or aggravation of acne by stress remain unclear, although possible mechanisms have been proposed. For instance, stress induces secretion of different neurotransmitters, cytokines, and hormones-CRH, cortisol, glucocorticoids-which have skin receptors and can aggravate several skin diseases [34,37,51,55,66] including acne [77,78]. Interesting, a recent study showed that skin diseases influence emotional status, through chemical mediators released by epidermal keratinocytes [22].…”
Section: Stress and Skin: A Specific Mechanismmentioning
confidence: 99%
“…While many studies have examined the effects of the physical stress associated with prolonged periods of exercise on the immune system [18,19,20], little attention has been given to the effects that the psychological stress associated with training may have on changes to host immunity. Psychological stress results in the enhanced production of corticosteroids and catecholamines [21] which are potent immunomodulators [22]. In animal models, high-stress environments have been associated with increased morbidity and mortality following bacterial and viral infection [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Not only do daily stressors lead to irritability, short temperedness, and a lack of concentration, but psychological stress can have long-term effects on an individual's sympathetic nervous system [7,9]. Psychological stress has been described as an adaptation to the fight or flight response [23]. With excessive activation of this response, elements such as cortisol, catecholamines and neuropeptides can produce negative effects on the immune system and can possibly contribute to disease onset and progression [23].…”
Section: Physical and Psychological Effects Of Stressmentioning
confidence: 99%
“…Psychological stress has been described as an adaptation to the fight or flight response [23]. With excessive activation of this response, elements such as cortisol, catecholamines and neuropeptides can produce negative effects on the immune system and can possibly contribute to disease onset and progression [23]. Extreme stress can even induce cardiac arrhythmias [24].…”
Section: Physical and Psychological Effects Of Stressmentioning
confidence: 99%